Elements of Service Influencing on the Success of Security Service Companies in Industrial Estates in the Central Region. - Lerttanasukhon, Pol.Sep-Lieutenant (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
Elements of Service Influencing on the Success of Security Service Companies in Industrial Estates in the Central Region The objective of this research was to study element of the service that influence the success of running security business of security service companies in the Central region of Thailand using survey questionnaires to collect data from 400 persons who were entrepreneurs, managers, or persons who were assigned by the companies who involved in using services from security companies. The author employed descriptive statistics to analyze data and employed inferential statistics to test hypothesis. The findings also found the respondents placed the most importance on the size of the security guard company followed by the number of security guard personnel, and responsibility on claims in order to the success of the company’s success. Regarding to characteristics of the security guard company, the findings found that brand image and popularity of the company is most importance in which the owner of the company is most importance, followed by referenced organizations that used the services, certifications, personnel development and trainings, standard certifications and experience in security guard business respectively. Regarding the efficiency of services which led to the success, The findings found that the respondents placed most importance on safety, efficiency of event responsiveness, and reliability of the services from the companies. Finally, the results revealed that process of service management was most importance followed by physical evident, services, service charges, distribution channel, marketing commination, and personal. The results of inferential statistics summarize the results found that Elements of service that affect the success of business operations of The security company in the industrial estate, the central region, consists of some factors of the characteristics of the management company, experience (b = 0.31) Service quality, trust (b = 0.14) and marketing mix of products or services (b = 0.22) Price of service charge (b = 0.15) on distribution channels (b = 0.29).The equation has 36 percent predictive power and can be written as an equation as follows. Y = 3.58+0.05 X01-0.02 X02+0.13 X03+0.01 X04+0.04 X05+0.31 X06**+0.12 X07+0.02 X08-0.04 X09+0.14 X10*+0.14 X11+0.22 X12**+0.15 X13*+0.29 X14**+0.07 X15 +0.01 X16+0.01 X17+0.03 X18 Article history : Received 11 November 2018 Revised 22 December 2018 Accepted 25 December 2018 SIMILARITY INDEX = 0.00